PENGARUH IDENTITAS BRAND DAN STRATEGI PENJUALAN BURGER KING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Amelda Pramezwary; Juliana Juliana; Billy Eagan; Feidora Jovanca Putri; Steven Setiadi (Universitas Bina Sarana Informatika, 2021)
Abstract - The pandemic period in 2020 has had a major impact on various sectors. no exception to the business sector that is growing rapidly such as the fast food business. This rapid development shows the growing intensity of competition in the fast food business. such as Burger King, AW, McDonald's, KFC, and so on. because of this, business owners must pay more attention to the desires of consumers who are diverse, change fast, and of course have different satisfaction values. The purpose of this study was to determine the effect of the Burger King brand identity and sales strategy on consumer purchasing decisions during the Covid 19 pandemic. The sample consisted of 105 respondents who had answered a questionnaire about the Burger King brand and the marketing strategy undertaken by Burger King. The samples that have been received are then analyzed for their answers, starting with descriptive analysis, basic statistics, and regression. After this analysis, the results obtained in the form of burger king brand identity have a significant effect, and the burger king sales strategy also has a significant effect. This shows that consumer purchasing decisions are influenced by brand identity and strategy.Keywords: Brand Identity, Sales Strategy, Consumer Purchasing Decisions